Pharmacist-assisted implementation of guideline recommendations for QTc monitoring during psychopharmacotherapy - a prospective, randomized feasibility study - Wien, Katharina; Klein, Jan Philipp; Rodenstein, Niels; Vogler, Julia; Tilz, Roland Richard; Thern, Julia; Borgwardt, Stefan (Frontiers in Psychiatry, 2025)
IntroductionMany psychotropic drugs potentially prolong the QTc interval. The aim of this study was to investigate the feasibility of the pharmacist-supported implementation of a new local guideline for QTc monitoring at a psychiatric department and to gather preliminary data on the effectiveness of this intervention.MethodsThe study was conducted as a prospective, randomized-controlled feasibility study at the inpatient service of a department of psychiatry. In the intervention group (IG), guideline-based monitoring of QTc intervals was supported by a clinical pharmacist. The control group (CG) was solely monitored by the treating physicians. The primary effectiveness outcome was the mean change in the QTc interval between admission (T0) and 30 days after admission (T1). The implementation ratio of guideline recommendations and the acceptability of the pharmacist support based on an online employee satisfaction survey were assessed as secondary outcomes.Results160 patients were recruited and randomly allocated to the IG (n = 75) or CG (n = 85). A total of 102 patients completed the trial (IG: n = 42, CG: n = 60). There was no significant difference in the mean change of the QTc interval from T0 to T1 between the two groups (p = 0.582). Guideline recommendations were significantly more often implemented in the IG than in the CG (78% vs. 37%, p = 0.004). 4 out of 15 (26.7%) physicians and 9 out of 45 (20%) nurses working on the wards responded to the online survey. Physicians and nurses were very satisfied with the pharmaceutical support.DiscussionPharmacist support of the implementation of a new guideline for QTc monitoring led to a higher rate of uptake of guideline recommendations but did not have a significant effect on the QTc interval. The responding physicians and nurses were very satisfied with this intervention. Future research using an adapted study design would be required to assess guideline adherence as the primary outcome and, secondarily, determine the effect of pharmacist support on cardiac outcomes.Clinical trial registrationGerman Clinical Trials Register: DRKS00033127, https://drks.de/search/de/trial/DRKS00033127.